High moisture corn for finishing steers - K. Bolsen; H. Ilg; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1979)
W used 135 yearling steers in two trials to compare dry with high moisture (HM) corn and soybean meal (SBM) supplement with urea supplement. Results of trail 1 (88 days) show HM corn either rolled or ensiled in a stave silo or ensiled whole in a fiberglass O2-limiting silo supported faster and more efficient gains than dry rolled, steam-flaked or HM-corn treated with a preservation. A 50% SBM+ 50% urea supplement tended to be used more efficiently than either 100% SBM or 100% urea supplements. In trial 2 (97 days) steers fed dry rolled corn or HM corn ensiled with a commercial additive had similar gains and 6.2% faster gains then steers fed HM corn ensiled without an additive. HM corn ensiled with the additive produced 7.1% more efficient steer gains than dry rolled corn and 4% more efficient gains than HM corn ensiled without the additive. An all-SBM supplement gave slightly better steer performance than all-urea supplement.
Keywords: Cattlemen' s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Corn; Steers